The role of television journalism in the production of political narratives: a comparative study Brazil/Colombia - Pérez Rodríguez, Germán; Romanini, Anderson Vinícius (Brazilian journalism research, 2022)
ABSTRACT – Based on the study of open TV news that covered the trials of former presidents of Colombia (Uribe) and Brazil (Lula), the article explores some of the editorial choices made by the two main news broadcasts in these countries (Jornal Nacional, from Brazilian Globo and Noticias Caracol, from Colombian Caracol) and analyzes the impact of these choices in the construction of narratives aimed at producing effects on public opinion. Despite the growing role of digital media in the societies analyzed, we argue that the amount of time devoted to the subject by these newscasts and the rhetorical resources used in the presentation of the news reveals the intentionality to thematize the public debate, even dominating the repercussion in other media and forcing a homogenized narrative of these facts, contributing to the political polarization and the spread of hate speech in the different spheres of the social system. RESUMO – A partir do estudo de noticiários de TV aberta que cobriram os julgamentos dos ex-presidentes da Colômbia (Uribe) e do Brasil (Lula), o artigo explora algumas das escolhas editoriais feitas pelos dois principais telejornais desses países (Jornal Nacional, da brasileira Globo; e Noticias Caracol, da colombiana Caracol) e analisa o impacto dessas escolhas na construção de narrativas voltadas a produzir efeitos na opinião pública. Apesar do crescente protagonismo das mídias digitais nas sociedades analisadas, arguimos que a quantidade de tempo dedicado ao assunto por esses telejornais e os recursos retóricos usados na apresentação das notícias revelam a intencionalidade de tematizar o debate público, dominando, inclusive, a repercussão nas demais mídias e forçando uma narrativa homogeneizada desses fatos, contribuindo para a polarização política e a propagação do discurso de ódio nas diversas esferas do sistema social. RESUMEN – A partir del estudio de noticias de TV abierta que cubrió los juicios de los expresidentes de Colombia (Uribe) y Brasil (Lula), el artículo explora algunas de las decisiones editoriales de los dos principales noticieros de estos países (Jornal Nacional, de la brasileña Globo y Noticias Caracol, de la colombiana Caracol) y analiza el impacto de estas elecciones en la construcción de narrativas orientadas a producir efectos en la opinión pública. A pesar del creciente papel de los medios digitales en las sociedades analizadas, sostenemos que el tiempo dedicado al tema por estos noticieros y los recursos retóricos utilizados en la presentación de la noticia revelan la intencionalidad de tematizar el debate público, dominando incluso la repercusión. en otros medios y forzando una narrativa homogeneizada de estos hechos, contribuyendo a la polarización política y la difusión del discurso de odio en los diferentes ámbitos del sistema social.